Analisis Manajemen Risiko di Masa Pandemi Covid-19 pada Perekonomian Indonesia - Ahmad Hamzah,; Dhea Adelia Anggraeni,; Maulida Luthfiah Hanum,; Putri Ayu Listiyaningrum,; Dwi Urip Wardoyo, (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
In early March 2020, the Indonesian government informed that there were two cases of Corona Virus or Covid-19 with the spread of this corona virus occurring rapidly and continuing to increase day by day. The transmission of this corona virus is quite significant because its spread has reached all countries in the world. . This study aims to find out what policies have been carried out by the government to deal with the current outbreak and see the economic impact that has occurred in Indonesia. This research shows that policies made by the government in handling Covid-19 can indirectly cause a slowdown in economic growth in Indonesia. The COVID-19 pandemic in Indonesia has resulted in a decrease in income, and even mass terminations. TheIndonesian government is expected to be more swift in dealing with the decline in economic growth in Indonesia caused by the Covid-19 pandemic.